A rat model for orthodontic translational expansive tooth movement. (24th June 2013) - Danz, J. C.; Dalstra, M.; Bosshardt, D. D.; Katsaros, C.; Stavropoulos, A.
Structured Abstract Objectives To present the development of an experimental model in rats for translational expansive tooth movement. Setting and Sample Section of Periodontology at Department of Dentistry Aarhus University. Twenty male Wistar rats in two pilot experimental settings plus seven animals without any intervention serving as controls. Material and Methods The second molar (group P1) or the second and third molar (group P2) in the maxillae of the animals were moved buccally using transpalatal β‐titanium springs. In the group P2, two spring types (high force and low force) and two preangulations (0° passive or 30° torsion moment) were tested. The amount and type of tooth movement achieved and the resulting skeletal effect were assessed on microCT images, histological analysis was performed on few selected specimens. Results Expansive translational root movement amounting half a tooth width was achieved. Comparison of the amount of tooth movement at the right and left side of the maxilla showed that the expansion was rather symmetrical in the P2 group. Skeletal widening of the maxilla contributed in the P2 group to approximately one‐third of the total root movement, whereas two‐thirds were dental movement. Conclusion With the model used in the P2 group, further research on translational expansive tooth movement and its effect on the periodontium can be pursued. In models for orthodontic expansion, it is strongly recommended to separately evaluate skeletal and dental effects.